Footprints: Stamping hallmarks of lung cancer with patient-derived models, from molecular mechanisms to clinical translation - Song, Yang; Wang, Yadong; Guan, Ai; Xue, Jianchao; Li, Bowen; Huang, Zhicheng; Zheng, Zhibo; Liang, Naixin; Yang, Yanlian; Li, Shanqing (Frontiers in Bioengineering and Biotechnology, 2023)
The conventional two-dimensional (2D) tumor cell lines in petri dishes have played an important role in revealing the molecular biological mechanism of lung cancer. However, they cannot adequately recapitulate the complex biological systems and clinical outcomes of lung cancer. The three-dimensional (3D) cell culture enables the possible 3D cell interactions and the complex 3D systems with co-culture of different cells mimicking the tumor microenvironments (TME). In this regard, patient-derived models, mainly patient-derived tumor xenograft (PDX) and patient-derived organoids (PDO) discussed hereby, are with higher biological fidelity of lung cancer, and regarded as more faithful preclinical models. The significant Hallmarks of Cancer is believed to be the most comprehensive coverage of current research on tumor biological characteristics. Therefore, this review aims to present and discuss the application of different patient-derived lung cancer models from molecular mechanisms to clinical translation with regards to the dimensions of different hallmarks, and to look to the prospects of these patient-derived lung cancer models.